Structure, Physicochemical Properties, Antioxidant and Antimicrobial Activities of Pectin Prepared by Enzymatic Hydrolysis of Premna ligustroides Hemsl. Leaves - LIU Sha, DENG Liling, ZHONG Geng, YANG Hongsheng (Shipin Kexue, 2023)
In this study, pectinase-extracted pectin (PPHP), mixed enzyme-extracted pectin (MPHP), and water-extracted pectin (WPHP) from Premna ligustrides Hemsl. leaves were prepared by pectinase-assisted extraction, pectinase and cellulase-assisted extraction and hot water extraction, respectively, and their molecular masses, monosaccharide compositions, infrared spectra, galacturonic acid contents, degrees of esterification were determined. In addition, their scavenging capacity against 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2’-azinobis-(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) radical cation and Fe3+ reducing power were assayed, and their antibacterial effects on Bacillus subtilis, Escherichia coli and Staphylococcus aureus were explored. The results showed that the yields of WPHP, PPHP and MPHP were 5.11%, 6.45% and 8.91%, respectively. WPHP belonged to high-ester pectin, while MPHP and PPHP belonged to low-ester pectin. The weight-average molecular mass of pectin in the leaves of Premna ligustrides Hemsl was reduced by enzymatic treatment. The contents of total phenols and total flavonoids in MPHP were 17.09 and 26.46 mg/g, respectively, higher than those in WPHP and PPHP. All three pectins had strong scavenging capacities against DPPH radical and ABTS radical cation, among which MPHP had the strongest antioxidant activity. The results of in vitro antibacterial activity showed that MPHP had the best antibacterial effect on Bacillus subtilis, Escherichia coli and Staphylococcus aureus. These results provide a basis for further searching for the material basis of the antibacterial activity of pectin from Premna ligustroides Hemsl. leaves, and are of significance for the in-depth development and utilization of pectin from Premna ligustroides Hemsl. leaves.